2020
DOI: 10.1002/pros.23988
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel suppresses immunotherapy efficacy of natural killer cells toward castration‐resistant prostate cancer cells via altering androgen receptor‐lectin‐like transcript 1 signals

Abstract: Background: Docetaxel is an effective first-line chemotherapy agent used in the treatment of castration-resistant prostate cancer (CRPC) patients. However, most times chemotherapy with docetaxel eventually fails due to the development of docetaxel resistance. Natural killer (NK) cells are the first line of defense against cancer and infections. NK cell function is determined by a delicate balance between signals received via activating and inhibitory receptors. The aim of this study is to explore whether the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…53 An inhibitory effect on natural killer cells by docetaxel has also been shown. 54 One possible explanation for our inability to identify a benefit from gemcitabine in tumors with CD8 high expression is that cotreatment with docetaxel may have canceled out any immune stimulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…53 An inhibitory effect on natural killer cells by docetaxel has also been shown. 54 One possible explanation for our inability to identify a benefit from gemcitabine in tumors with CD8 high expression is that cotreatment with docetaxel may have canceled out any immune stimulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Mathew et al suggested that CLEC2D might allow prostate cancer cells to evade the immune system by inhibiting natural killer cells [ 48 ]. Tang et al suggested that CLEC2D can enhance prostate cancer resistance to docetaxel [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using the coculture system, Galustian et al confirmed that PCa cells had a stronger ability to enhance IL-15-mediated expansion and cytotoxicity of NK cells than non-cancerous cell lines (PNT2 and WPMY-1) (Sakellariou et al, 2020), suggesting that the human body applies a protective strategy against PCa by activating NK cells. Accordantly, another study showed that AR could transcriptionally regulate the expression of NK inhibitory ligand LLT1 (lectin-like transcript 1) in PCa cells (Tang et al, 2020). Castration led to a short decline of AR activity so that the LLT1 level was reduced, eventually contributing to the expansion and activation of NK cells.…”
Section: The Role Of Androgen Receptor In Cross Talk Between Natural Killer Cells and Prostate Cancermentioning
confidence: 94%